Evaluation of Counseling Services at Student Counseling Centers in Universities Under the Supervision of the Ministry of Science, Research, and Technology - Ahmadi Dehrashid, Fatemeh; Salimi, Jamal; Isanejad, Omid (International Journal of Education and Cognitive Sciences, 2025)
Purpose: The present study aimed to evaluate the counseling services provided by university counseling centers operating under the supervision of the Ministry of Science, Research, and Technology. Methods and Materials: From a methodological perspective, this research is an exploratory mixed-method study utilizing both quantitative and qualitative approaches. Data analysis was conducted in two formats, qualitative (content analysis) and quantitative, depending on the nature of the research questions. The research sample consisted of 17 experts and specialists in counseling services and 400 students currently enrolled in universities under the supervision of the Ministry of Science, Research, and Technology. Findings: The findings revealed that female students and those who received services from non-residential counseling centers expressed greater satisfaction with the counseling services. Conclusion: The results indicated that student counseling centers, as one of the essential components of universities, play a central role in enhancing the quality of higher education. These centers significantly contribute to increased academic motivation and personal and social development by providing psychological, academic, and career services.